Thimet oligopeptidase as a potential CSF biomarker for Alzheimer's disease: A cross‐platform validation study - Yanaika S. Hok‐A‐Hin; Katharina Bolsewig; Daimy N. Ruiters; Alberto Lleó; Daniel Alcolea; Afina W. Lemstra; Wiesje M. van derFlier; Charlotte E. Teunissen; Marta delCampo (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring, 2023)
Abstract INTRODUCTION Our previous antibody‐based cerebrospinal fluid (CSF) proteomics study showed that Thimet oligopeptidase (THOP1), an amyloid beta (Aβ) neuropeptidase, was increased in mild cognitive impairment with amyloid pathology (MCI‐Aβ+) and Alzheimer's disease (AD) dementia compared with controls and dementia with Lewy bodies (DLB), highlighting the potential of CSF THOP1 as an early specific biomarker for AD. We aimed to develop THOP1 immunoassays for large‐scale analysis and validate our proteomics findings in two independent cohorts. METHODS We developed in‐house CSF THOP1 immunoassays on automated Ella and Simoa platforms. The performance of the different assays were compared using Passing–Bablok regression analysis in a subset of CSF samples from the discovery cohort (n = 72). Clinical validation was performed in two independent cohorts (cohort 1: n = 200; cohort 2: n = 165) using the Ella platform. RESULTS THOP1 concentrations moderately correlated between proteomics analysis and our novel assays (Rho > 0.580). In both validation cohorts, CSF THOP1 was increased in MCI‐Aβ+ (>1.3‐fold) and AD (>1.2‐fold) compared with controls; and between MCI‐Aβ+ and DLB (>1.2‐fold). Higher THOP1 concentrations were detected in AD compared with DLB only when both cohorts were analyzed together. In both cohorts, THOP1 correlated with CSF total tau (t‐tau), phosphorylated tau (p‐tau), and Aβ40 (Rho > 0.540) but not Aβ42. DISCUSSION Validation of our proteomics findings underpins the potential of CSF THOP1 as an early specific biomarker associated with AD pathology. The use of antibody‐based platforms in both the discovery and validation phases facilitated the translation of proteomics findings, providing an additional workflow that may accelerate the development of biofluid‐based biomarkers.